Peran kurikulum Dan Fungsi kurikulum - Farhany Zahra Qurrata Ainy; Anne Effane (Universitas Djuanda, 2023)
Curriculum is something that is planned as a guideline for achieving educational goals. Usually what is planned is the ideas, aspirations of humans or citizens to be formed. What can be realized is called a real curriculum, while what cannot be realized is actually still in the form of ideas The 2013 curriculum is a simplification and thematic-integrative curriculum with added study hours. This is intended to encourage students or students to have better abilities in observing, asking questions, reasoning, and communicating what they get or know after studying the subject matter, and make our students have competence in words, skills, and knowledge. which is much better. They will be more creative, innovative, and more productive, so they can be successful in facing various problems and challenges in their day, and have a better future. What can be realized in reality is called a real curriculum, what cannot be realized turns out to be an idea. At least three very important curriculum roles, namely the conservative role. critical role or evaluative and creative roles. While the curriculum function consists of an adjustment function. integration function, differentiation function, preparatory function, selection function, and diagnostic function. The method used in this research is qualitative research with the type of literature search usually used for searches that are carried out in detail, complete and explain the material in depth. In a literature search, data can be analyzed directly from the original source. The most important information in this article is educational books, multicultural books, laws, digital books, web sites and journal articles related to the topics discussed. At the data analysis stage, the textbook collection was used first. Such as educational curriculum books, multicultural books, and search for related topics on Google Scholar. Then, sorting the findings data to display, then check, and analyze so that conclusions can be drawn. Keywords Curriculum, Role and Fungal